The Influence of Service Quality, Prices and Promotions on Student Satisfaction in Following the Course at the Study Institution Mr. Bob English Club Pare Kediri - Rafikhein Novia Ayuanti; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this era of globalization, there are various types of education patterns, one of which is non-formal education. The Mr.BOB course institution is one of the most popular course institutions. Whether it is seen in the testimonials of its members or whether the institution recognizes it and tries to always maintain it. This research examines the influence of service quality, price, and promotion on student satisfaction when taking courses at the Mr. Bob English Club Pare Kediri tutoring institution. This type of research uses quantitative and causal methods (causal research).